Perception and knowledge of organic farmers about pests and natural enemies - P. L. P. Teixeira; F. A. Spagnuolo; J. M. Ferreira; T. S. Telles (Brazilian Journal of Biology)
Abstract Knowledge about pests is essential for agriculture, as they can cause significant damage to crops. However, it is equally important to understand the natural enemies that assist farmers in controlling pest insect populations, thereby reducing the need for inputs and promoting production sustainability. The ability to recognize and identify natural enemies is even more relevant for producers who employ environmentally friendly and agroecological-based management techniques, such as biological pest control. Thus, the objective of this study was to assess the level of knowledge of organic and agroecological transition farmers in northern Paraná, Brazil, regarding the identification of pests and natural enemies, aiming to understand how the socioeconomic profile of the respondents influences their understanding of the ecological relationships between insects in the agroecosystem. To this end, a survey-type research was conducted in which 41 organic or agroecological transition farmers were interviewed in person. Farmers, in general, were able to recognize and identify pests in their crops however, they did not achieve the same success regarding natural enemies, highlighting their lack of awareness of the ecological role of this group of insects in the context of integrated pest management. It was observed that the species with the highest identification accuracies were: Aphis gossypii (100%), Bemisia tabaci (100%), Tuta absoluta (97.6%), Frankliniella sp. (95.1%), and Agrotis ípsilon (92.7%), all categorized as pests. On the other hand, the species with the lowest identification accuracies were: Lebia concinna (53.7%), Callida sp. (53.7%), Allograpta sp. (36.6%), Orius spp. (19.5%), and the bug from the Reduviidae family (17.1%), all belonging to the natural enemies group. It is evident that technical assistance and rural extension actions should focus on training and educating farmers dedicated to organic production about biological control management through the conservation and creation of habitats for natural enemies on their properties.